Platelets and Antiplatelet Medication in COVID-19-Related Thrombotic Complications - Schrottmaier, Waltraud C.; Pirabe, Anita; Pereyra, David; Heber, Stefan; Hackl, Hubert; Schmuckenschlager, Anna; Brunnthaler, Laura; Santol, Jonas; Kammerer, Kerstin; Oosterlee, Justin; Pawelka, Erich; Treiber, Sonja M.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Coronavirus disease 2019 (COVID-19) induces a hypercoagulatory state that frequently leads to thromboembolic complications. Whereas anticoagulation is associated with reduced mortality, the role of antiplatelet therapy in COVID-19 is less clear. We retrospectively analyzed the effect of anticoagulation and antiplatelet therapy in 578 hospitalized patients with COVID-19 and prospectively monitored 110 patients for circulating microthrombi and plasma markers of coagulation in the first week of admission. Moreover, we determined platelet shape change and also thrombi in postmortem lung biopsies in a subset of patients with COVID-19. We observed no association of antiplatelet therapy with COVID-19 survival. Adverse outcome in COVID-19 was associated with increased activation of the coagulation cascade, whereas circulating microthrombi did not increase in aggravated disease. This was in line with analysis of postmortem lung biopsies of patients with COVID-19, which revealed generally fibrin(ogen)-rich and platelet-low thrombi. Platelet spreading was normal in severe COVID-19 cases; however, plasma from patients with COVID-19 mediated an outcome-dependent inhibitory effect on naïve platelets. Antiplatelet medication disproportionally exacerbated this platelet impairment in plasma of patients with fatal outcome. Taken together, this study shows that unfavorable outcome in COVID-19 is associated with a profound dysregulation of the coagulation system, whereas the contribution of platelets to thrombotic complications is less clear. Adverse outcome may be associated with impaired platelet function or platelet exhaustion. In line, antiplatelet therapy was not associated with beneficial outcome.